THEORY OF FUNCTIONS OF MULTIMEDIA HANDBOOKS - WALAT, Wojciech (Trends in education, 2008)
The totality of pedagogical phenomena is the object of researchers of theory multimedia handbooks, what join them with processes pedagogical realized in relationship with such aid of development of psyche pupils, to be able to undertake the consequential with receipt of mediumistic transfer tasks individually. This transfer speaks in learning the newest technologies of education, the passed on through the selective and active receipt of content the media's as well as in skill creating of educational program.
Keywords: theory of pedagogy; handbook; multimedia; ICT